Көші-қон үрдісін реттейтін заңдардың қалыптасуы - Божқараұлы, А. (ҚарМУ басп, 2010)
Проблема миграции в Казахстане характеризуется особой сложностью, так как в ней переплетены не только правовые вопросы, но и вопросы социологии, демографии, политической экономии, этногео- графии, трудовых ресурсов в экономике. Среди них юридический аспект занимает особое место, по- скольку от надлежащего правового обеспечения, регулирования и организации процессов миграции зависит решение других вопросов, имеющих существенное значение для жизнедеятельности обще- ства. The problem of migration is characterizing with special complexity, as it covers not only legal aspects, but also the problems of sociology, demograthy, political economy, ethnogeography, the problems of labor resources in the economics. The legal aspect have the special important place, because the migration is closely connected with the legal security, regulation and organization of migration processes, from which depends other problems of essential value for living conditions of the society.